Model of Unmanned Ground Vehicle - Václav KRÁLÍK (Wojskowa Akademia Techniczna, 2010)
The paper deals with utilization of the laser rangefinder for navigation and mapping of unknown indoor environment. The navigation algorithm is based on comparison of two pictures of the unknown space and gain of the correlation function maximum. The 2D position change of the rangefinder is calculated as a maximum of the correlation function. The goal is to improve the accuracy of odometric and inertial methods for localization and navigation of a robot system in an indoor environment.
Keywords: Sterowanie pojazdem lądowym